(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article addresses the challenges of balancing scientific research with creative practice within fine arts higher education. Given the shifting demands of the modern labor market, future art educators must develop not only technical artistic proficiency but also analytical thinking and methodological competence. The paper analyzes existing curricula, course structures, and prevailing attitudes toward academic research in higher education institutions. Drawing on local and international studies, it highlights the importance of interdisciplinary integration, mentor-student (ustoz-shogird) traditions, faculty-student research collaborations, and innovative educational models. Ultimately, the study offers practical recommendations for establishing a robust academic environment that effectively bridges theory and practice in fine arts education.